جمالية الاظهار في مقام اﻹضار في دواني علي بن ابي طالب والشافعي - منصور وقاص (جامعة البليدة2؛كلية الاداب واللغات, 2024)
هار في مقام ار الﻼة ﻷسلب اﻹ ة واﻷس ّ ائف الال ّ ام ع الل ّ يهف ها ال إلى إماة الل ّ ع العي ّ اﻹضار ض ساقات نة ملفة، وﻻسفاء ذل عنا إلى اخار ديان شع م نفائ ال ب أبي ّ ها: ديان أبي ال علي. ّ ال، وديان م ب إدر الافعي اءة ث مفقة، ﻻسا غي ع ق ّ اده ب مقل ع وف كا يهف ال إلى جع شات ها الض ع ها الض ّ وأن ّ م الاضع الي تل ّ ع ّ ى فها الاوجة ب الات ال ّ اثة الع ات ة القة، والع انة ال ّ الل أسلب اﻹهار في مقام اﻹضار ه خوج على مقى اه الال، وه ّ إذ إن ، ية ما عف ع ا – الﻼغ ق- الي اني الي عف العول أو اﻻناح ع اﻷداء ال ّ رس الل ّ الفة الاه، وفي ال امات تاة، ﻻسل خﻼل ، م ّ ح ت تاشا وتامﻼ لعلم العة القة عها مع ع َ ةّ ث ّ أن ُال ة ولانات ّ اولّ الي اﻷسلة وال ّ غّ رس الل ّ م علم في ال ّ ا مع ع ما اس كا أن لها تقارا وتاس .ّ ال ّ وف ال أن ار أسلب اﻹهار في مقام اﻹض لّ ق ش ة بﻼة و اهة أسل أبي ب ّ ارزة في ديان علي ّ افعي ّ ال وال ح أفاد م- ان يّ ي ورد فها في قائ ال ّ ة ال ّ اقات ال ّ خﻼل ال - ا لا ئف جالة ون بﻼة، ترك الوق . Research Summary: This research aims to uncover the aesthetic subtleties and rhetorical secrets of the style of display in the position of ambiguity within different grammatical contexts. To accomplish this, we chose two collections of poetry from the gems of Arabic poetry: the collection of Abu Al-Hasan Ali bin Abi Talib, and the collection of Muhammad bin Idris Al-Shafi’i. The research also aims to collect the fragments of this topic and separate it into an independent study that eliminates the need to read separate research, especially since this topic is considered one of the topics in which the marriage between ancient Arab heritage achievements and modern linguistic data is evident, as the method of display in the position of implicitness is a departure from the apparent requirement. The situation, which is what is known among rhetoricians - in the past - as contradicting what is apparent, and in the modern linguistic lesson it is known as turning away from the ideal performance of communicative obligations, as it has become clear through research that there is coexistence and integration of the ancient Arabic sciences with each other, and they also have closeness and boldness with each other. New sciences in the modern linguistic lesson, such as stylistics, pragmatics, and textual linguistics. The research revealed that the method of display in the position of ambiguity constituted a prominent rhetorical and stylistic phenomenon in the collections of Ali bin Abi Talib and Al-Shafi’i, where it provided - through the regular contexts in which it appeared in the poems of the two collections - aesthetic charms and rhetorical jokes, perceived with taste.
دراسة نحوية بلاغية
Keywords: مقام الاضمار; جماليات الاظهار; ابي طالب و; الشافعي